Best bear ever! : a little year of - Climo, Liz (Running Press, 2018)
Life can be a real bummer, but Climo knows people need to laugh. She started doing comics on social media, just to tell jokes. Feedback indicated that her comics offered a bit of distraction in the midst of sadness. Now Climo's work has been collected, and her characters Bear and Rabbit join their other friends from spring to winter, celebrating the seasons, and knowing that in friendship any time of year can be the best ever. -- adapted from introduction and back cover